Performance of Volunteer Firefighters at the Nunukan Regency Fire Management and Rescue Service - Aristra Pratama Sanmigo; Abdul Samad; Mujahid (Journal GoodWill, 2025)
This research aims to analyze the performance and factors hindering the performance of volunteer firefighters at the Fire and Rescue Service of Nunukan Regency, as well as to identify solutions to overcome these obstacles. This research uses a qualitative method with a descriptive approach. Data were collected through in-depth interviews with five key informants, namely the Volunteer Coordinator, Firefighting Volunteers, community members involved in empowerment programs, and fire victims. The results of the study show that firefighting volunteers demonstrate a high level of dedication in responding to fires, especially in remote areas. They play a crucial role in reducing the impact of fires by providing quick responses and extinguishing the fire before the official firefighting team arrives. However, the main challenges they face are the limited equipment and lack of advanced training to handle large and complex fires. Coordination with the Fire Department and other related agencies is generally good, although there are some communication barriers that need improvement. Overall, while the volunteers show good performance, improving training, equipment, and coordination will further enhance their effectiveness in firefighting efforts